(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wood is one of the most widely spread building and manufacturing materials, which has been used from antiquity till nowadays. There are many examples for the application of timber in contemporary design, however, some of the most attractive ones are those related to the development of sustainable design. Growing product and spatial design by modelling construction and shape during plant growth is a method experimented in for a long time. In contemporary design these explorations are motivated and justified not by the desire to rule over nature, but by the ambition to take care for it and use resources in a sustainable manner.